Music of Sounds - Ibrahim, Ibrahim Abdalla; Ahmed, Jamal Ibrahim Abdalrahman; Zahid, Fatima Omer Alsayer; Fadlala, Mohammed Abdalla Mohammed (Journal of Arabic Language Sciences and Literature, 2023)
The study investigated rhymes and rhythm in Arabic poetry, adopting analytical, descriptive approach, to probe the hidden features, and to reveal, melody. various aspects of rhythm and rhymes in Arabic were reviewed. The findings showed that the Arabic rhythms is affected by and interacted with many factors. some of these are rhetorical, and some are prosodic, linguistic, and morphological. The findings also showed that the rhymes differ according whether it is in the form of poetry or prose, and that the rhetorical adjacency is one of the best types of repetition. moreover, the psychological and emotional tendencies of the poet affect his choices. These findings bring the study of rhymes into the field of medical studies,Especially those concemed with the brain, nevese, and psychological studies. The researchers suggested introducing acoustic studies within psychological studies by using acoustic laboratory technology. They also commended applying the study to both poetry and prose.
Keywords: sounds; rhymes; allegories; rhythms; music